A critical examination of the Financial Mechanism as adopted in the Convention on Biological Diversity (CBD) from a developing countrys perspective (Northern University Journal of Law, 2014)
The main objective of this article would be to examine the financial mechanism of the CBD for the purpose of measuring its efficiency to ensure the Convention's implementation in the developing countries. The more international environmental law advances the more it is realized that normative provisions are hardly able to bring any good to the environment, if it is not substantiated by effective compliance mechanisms. The Convention on Biological Diversity is no exception to this realization and in tune with that the CBD adopted some in-built mechanisms e.g. financial mechanism, technology transfer etc. But how much is the financial mechanism, the most important of these, efficient to prompt the developing countries to comply with the Convention? This article will search for the answer to this question which is especially intriguing given the challenge of developing countries to strike a balance between developmental and conservation needs. DOI: http://dx.doi.org/10.3329/nujl.v1i0.18526 Northern University Journal of Law Vol.1 2010: 70-81